1986
DOI: 10.1203/00006450-198604000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic in Utero Hypoxia on the Pulmonary Vasculature of the Newborn Guinea Pig

Abstract: ABSTRACT. This report analyzes the effect on pulmonary vascular structure and function in the newborn guinea pig of chronic fetal hypoxemia, induced by maternal hypobaric hypoxia (380-420 torr) without direct interference with the utero-placental blood flow. Six pregnant guinea pigs were maintained in hypobaric chambers, 10 newborns from their litters being the hypoxic group. Twenty newborns from the litters of 10 pregnant guinea pigs maintained in air were the control group. After spontaneous delivery cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 8 publications
3
18
0
Order By: Relevance
“…This work establishes a link between intrauterine events and the failure of postnatal adaptation of the pulmonary circulation at birth, and demonstrates histologic features and pathophysiologic abnormalities characteristic of human persistent pulmonary hypertension of the newborn (6,7,10,14,15). Although previous studies have suggested that fetal events may alter either vascular reactivity (31,32) or structure (1 1-13, 16,17), more recent studies have failed to confirm these observations (18)(19)(20) (16). Similarly, partial ductus closure secondary to cyclooxygenase inhibition (15) or ligation (16,17,33) leads to similar structural lesions of small pulmonary arteries.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This work establishes a link between intrauterine events and the failure of postnatal adaptation of the pulmonary circulation at birth, and demonstrates histologic features and pathophysiologic abnormalities characteristic of human persistent pulmonary hypertension of the newborn (6,7,10,14,15). Although previous studies have suggested that fetal events may alter either vascular reactivity (31,32) or structure (1 1-13, 16,17), more recent studies have failed to confirm these observations (18)(19)(20) (16). Similarly, partial ductus closure secondary to cyclooxygenase inhibition (15) or ligation (16,17,33) leads to similar structural lesions of small pulmonary arteries.…”
Section: Discussionmentioning
confidence: 58%
“…Finally, data from animal studies suggest that chronic fetal hypertension or hypoxia may cause structural lesions similar to those found in humans with PPHN (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, recent attempts to demonstrate physiologic or histologic abnormalities after chronic intrauterine hypoxia or indomethacin treatment have not supported this hypothesis, and mechanisms contributing to the initiation and progression of the pulmonary vascular abnormalities of PPHN are unknown (18)(19)(20). In addition, no study has actually linked intrauterine events with altered perinatal pulmonary vasoreactivity, the inability to achieve or sustain a drop in pulmonary vascular resistance at birth, and structural vascular changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, pulmonary arterial pressure averaged less than systemic on room air, pulmonary blood flow was not measured, and hypoxemia was not reported. Chronic intrauterine hypoxia alone did not cause pulmonary hypertension in newborn guinea pigs (24).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, investigators have placed pregnant animals in environments with low Fi,,, embolized the placenta, or partially occluded the umbilical cord (24)(25)(26). These approaches should divert even more of the right ventricular output away from the lungs in the fetus (7).…”
Section: Discussionmentioning
confidence: 99%
“…66 Several experimental models have been used to explore the pathogenesis and pathophysiology of PPHN. 63,[67][68][69][70] PH induced experimentally by early closure of the ductus arteriosus in fetal sheep alters lung vascular reactivity and structure, causing the failure of postnatal adaptation at delivery and providing a useful model of PPHN. Studies with this model show that chronic hypertension without high blood flow impairs fetal lung vascular structure and function.…”
Section: Impaired Lung Vascular Development In Pediatric Pah General mentioning
confidence: 99%